2001
DOI: 10.1215/s0012-7094-01-11023-5
|View full text |Cite
|
Sign up to set email alerts
|

Logarithmic differential forms on p-adic symmetric spaces

Abstract: We give an explicit description in terms of logarithmic differential forms of the isomorphism of P. Schneider and U. Stuhler relating de Rham cohomology of p-adic symmetric spaces to boundary distributions. As an application we prove a Hodgetype decomposition for the de Rham cohomology of varieties over p-adic fields which admit a uniformization by a p-adic symmetric space.with the obvious face and degeneracy maps (where H i denotes a linear form defining H i ). It is shown in [SS] that there is a natural isom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
2

Year Published

2002
2002
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 10 publications
0
24
0
2
Order By: Relevance
“…Hdg ) j≥0 and (F r Γ ) r≥0 are opposite to each other whenever F admits an integral lattice has been shown earlier by Iovita and Spiess [18] by completely different methods, and yet another proof is due to Alon and de Shalit.…”
Section: The Hodge Filtration (Fmentioning
confidence: 83%
“…Hdg ) j≥0 and (F r Γ ) r≥0 are opposite to each other whenever F admits an integral lattice has been shown earlier by Iovita and Spiess [18] by completely different methods, and yet another proof is due to Alon and de Shalit.…”
Section: The Hodge Filtration (Fmentioning
confidence: 83%
“…Iovita and Spiess [15] first proved all these conjectures for the trivial G-representation M = K (and there is another proof by Alon and de Shalit), later we proved it furthermore for the standard representation M = K d+1 of G and its dual [13]. In [11] we showed that if Φ is as in (a)(v) then the filtration F • Γ is just the slope (resp.…”
Section: Introductionmentioning
confidence: 63%
“…We may pass to the base field extension K →K. Then we have inclusions of sheaf complexes Remarks: (1) The decomposition (51) was proven for the trivial representation M = K for the first time by Iovita and Spiess [10]. Our present proof appears to provide a geometric underpinning of the one given in [10].…”
Section: Remarksmentioning
confidence: 70%
“…every element of H 0 (X, Ω s X ) ⊗ K, is in fact logarithmic, in particular it is closed. Thus H 0 (X, Ω s X ) ⊗ K must be the space of bounded logarithmic differential s-forms on X studied in [10] (if char(K) = 0).…”
Section: Coherent Cohomology Via Logarithmic Differential Formsmentioning
confidence: 99%